Oral History Interview: Clifford Wagy interviewed by Camille Gavin - Wagy, Clifford; Gavin, Camille
Clifford Wagy describes early Bakersfield history from a ranching perspective. Some interesting information on Miller & Lux and downtown Bakersfield.